Erzeugung alternativer flüssiger Kraftstoffe im zukünftigen Energiesystem. Issue 1 (18th January 2018) - Dietrich, Ralph‐Uwe; Albrecht, Friedemann; Pregger, Thomas
Abstract: This paper discusses the potential need for renewable liquid fuels, evaluates large‐scale production options using renewable power, biomass, and other carbon sources, and considers system analysis of the feedstock development. A case study for technical, economic, and ecological evaluation uses rigorous process simulation and the cost evaluation tool TEPET for high level transparency from a scientific point of view.